The Realm of Enhanced Agency: A Choice-Based Account of Heavenly Freedom - Hoque, Robbie (AGATHEOS – European Journal for Philosophy of Religion, 2025)
Free will theodicies that rely on a good afterlife to explain how earthly evils are ultimately outweighed or defeated are challenged by what Simon Kittle has termed the lack of value problem concerning heavenly freedom: that a heaven with no freedom to make good and evil choices is not a supreme good that could justify God’s creation of evil. I take up Kittle’s suggestion that this problem can be addressed by a choice-based account of heavenly freedom which gives some idea of how the types and number of choices an agent might face in heaven add up to a level of freedom that it would be desirable to have. While Christian concepts of divine-human union typically prioritise non-choice-based accounts of heavenly existence, I argue that the notion of a realm of enhanced of agency, derived from a good-maximising view of an omniperfect God’s creative purpose, provides an account of the goods that might exist in heaven and how choices between them could be supremely valuable.